Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ped.15145
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and outcome of acute recurrent pancreatitis and chronic pancreatitis

Abstract: Background Owing to the lack of data, we aimed to determine the etiology and outcome of acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) in children in Southeast Asia. Methods This retrospective study was conducted at a university hospital in Bangkok, Thailand. We included patients aged <18 years who were diagnosed with pancreatitis from 2000 to 2021. Results Among 155 patients with pancreatitis, 21 (13.5%) were diagnosed with either ARP (n = 7) or CP (n = 14). Clinical manifestations of CP inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Several studies have described the AAP phenotype and suggested underlying risk factors, which include older age at ALL diagnosis, higher cumulative dose of asparaginase, and certain host genome variants 12–16 . Potential long‐term sequelae (e.g., organ‐related symptoms, exocrine deficiency, and diabetes mellitus [DM]) could have a negative impact on growth, overall health, and quality of life, 17–21 however, this has not previously been systematically explored. Symptoms of pancreatic dysfunction may be unspecific and thus misinterpreted unless targeted screening is performed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described the AAP phenotype and suggested underlying risk factors, which include older age at ALL diagnosis, higher cumulative dose of asparaginase, and certain host genome variants 12–16 . Potential long‐term sequelae (e.g., organ‐related symptoms, exocrine deficiency, and diabetes mellitus [DM]) could have a negative impact on growth, overall health, and quality of life, 17–21 however, this has not previously been systematically explored. Symptoms of pancreatic dysfunction may be unspecific and thus misinterpreted unless targeted screening is performed.…”
Section: Introductionmentioning
confidence: 99%
“…The increased overall survival of ALL, combined with an intensified use of ASNase in the treatment of ALL, has resulted in a growing number of long‐term AAP survivors, and calls for a focus on potential long‐term effects. Such potential late effects of ASNase treatment include morphological changes in the pancreas accompanied with recurring painful pancreatitis episodes, gastrointestinal symptoms, and endocrine and exocrine deficiency 2,9,10 that may affect growth, puberty, daily function, and health‐related quality of life 11–14 . As completion of ASNase treatment is associated with superior overall survival, 15,16 patients are commonly re‐exposed to ASNase after resolution of ASNase‐related toxicities, including AAP, depending on the anticipated risk of leukemic relapse and the severity of the toxicity 3,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Such potential late effects of ASNase treatment include morphological changes in the pancreas accompanied with recurring painful pancreatitis episodes, gastrointestinal symptoms, and endocrine and exocrine deficiency 2,9,10 that may affect growth, puberty, daily function, and health-related quality of life. [11][12][13][14] As completion of ASNase treatment is associated with superior overall survival, 15,16 patients are commonly re-exposed to ASNase after resolution of ASNase-related toxicities, including AAP, depending on the anticipated risk of leukemic relapse and the severity of the toxicity. 3,17 ASNase re-exposure is associated with a 40%-50% risk of developing a second AAP episode, 18 with potential aggravation of long-term sequelae; however, detailed information on the risk of sequalae after a second AAP is not yet available.…”
mentioning
confidence: 99%